Thermo elasticity solution of sandwich circular plate with functionally graded core using generalized differential quadrature method. (February 2016) - Alibeigloo, A.
Abstract: Bending analysis of sandwich circular plate with functionally grade core layer subjected to thermo-mechanical load is carried out using generalized differential quadrature (GDQ) method. The facing layers are made by metal and ceramic whereas the core layer is functionally graded materials composed of metal and ceramic material with distribution according to exponential function. Sandwich plate has various edges boundary conditions. Temperature distribution in three dimensions is obtained by solving heat conduction governing equation analytically. From combination of three dimensional governing equilibrium equations and constitutive relations, state space equations are derived. Applying GDQ method to the state space equations along the radial direction, semi-analytical solution can be obtained. After checking the convergence of the present approach, validation is carried out by comparing numerical results with the available results in open literature. Moreover, parametric study is presented to show the effects of the gradient direction, outer radius to thickness ratio, edges boundary conditions on the thermoelastic behavior of sandwich annular plates.